HUBUNGAN ANTARA OPTIMISME DENGAN KUALITAS HIDUP PADA PASIEN KANKER - Ficka Faradila Nufus; Farhati M. Tatar (State Islamic University (UIN) Ar-Raniry, 2017)
Cancer is one of the leading causes of death around the world that will have an impact on individual psychological. Psychological reactions that appear in cancer patients is reported to be an important factor on quality of life. Quality of life is defined as an advantage or merit in aspects of life such as survival and longevity. One determinant of the quality of life of individuals involved disposition of optimism, which looks optimistic cancer patients have better psychological health and better quality of life. The purpose of this study was to examine the relationship between optimism and quality of life in cancer patients. The participants were 60 cancer patients (17 male and 43 female) who were selected by using quota sampling method. Data were collected by using Life Orientation Test-Revised dan Quality of Life Inventory. The results of data analysis used Spearmen Correlation Technique showed correlation coefficient (r) = 0,344 with a significant value (p) = 0.63 (p > 0.05) It can be interpreted that there was no significant relationship between optimism and quality of life in cancer patients. In conclusion, the results showed that optimism has not significantly related to quality of life in cancer patients.